In vitro differences of neonatal and later postnatal keratinocytes and dermal fibroblasts - Krejčí, E; Kodet, O; Szabo, P; Borský, J; Smetana, K; Grim, M; Dvořánková, B (Physiological research, 2015)
Skin healing process is postnatally always associated with scarring of various extent. Based on the clinical experience of plastic surgeons, the healing after lip cleft reconstruction is surprisingly almost scar-less when it is carried out within a few first days after birth. This phenomenon is not seen in delayed cases. In order to decipher causative mechanism, we have isolated and studied principal cell populations, keratinocytes and fibroblast, from residual tissue samples after reconstructive operation (N=39) performed at various age (0-9 years). These cells play the pivotal role in the healing and that is why we focused on description of their phenotype and also functionality with respect to age. We have identified a population of remarkably small cells in explants from newborns (day 0-10). These small cells were strongly positive for markers of low differentiated keratinocytes, keratin-8 and -19, and moreover also for vimentin. In the explants cultures from older babies this population was missing. Fibroblasts from newborns and older patients differed namely in terms of nestin expression and also in the production of extracellular matrix components. We conclude that in vitro described properties of keratinocytes and fibroblasts in newborns could participate on the almost scar-less wound healing in earliest neonatal period.
Keywords: buněčná diferenciace; novorozenec; Infant, Newborn; Infant; Humans; fyziologie kůže; kojenec; dítě; Child; Keratinocytes; Female; kůže; stárnutí; keratinocyty; lidé; Aging; předškolní dítě; Skin Physiological Phenomena; ženské pohlaví; Male; Cell Differentiation; fibroblasty; mužské pohlaví; Child, Preschool; Skin; Fibroblasts